Observing hepatic steatosis with a commercially viable two-photon fluorogenic probe - Han, Jingjing; Lee, Hyo Won; Chen, Yahui; Li, Haidong; Kim, Hwan Myung; Yoon, Juyoung (Materials Chemistry Frontiers, 2022)
The key mechanism of lipid droplet-related diseases and polarity remains undetermined due to a scarcity of research on numerous condition models. We developed a conventional donor-acceptor fluorogenic probe with the untwisted intramolecular charge process. It is near-infrared-excited two-photon LD-specific and polarity-sensitive. This probe can detect dynamic changes of LD polarity in cancer cells and visualizes aberrant LD polarity in hepatic steatosis models. In the future, it could be beneficial for clinical diagnosis of LD polarity-related symptoms and to track the origin of lipid droplets and to monitor polarity-relative subcellular organelles. This journal is
Keywords: Charge process; Condition; Donor/acceptor; Fluorogenic probes; Hepatic steatosis; Intramolecular charge; Lipid droplets; Near Infrared; Near-infrared; Two photon